Effects of Ramadan environment on nicotine dependence among Malay male smokers at a municipal council, Selangor, Malaysia - Zulkifley, Nuraisyah Hani (2017)
Introduction: Nicotine dependence is one of the major issues that are causing massive failure in the effort to stop or quit smoking. Various strategies and preventive methods have been planned and implemented, but smoking is still a major public health issue in Malaysia. Fasting during Ramadan is one of the major challenges for smokers to abstain from smoking.